Family Visit at 207 Geneva Avenue, Huntington Beach - Watkins, Howard::::::::: (1984)
Howard Watkins with Adam Watkins and Albert Watkins each listening on their crystal radio sets Albert made his set in 1935 when attending Huntington Beach High School